2018
DOI: 10.3390/cancers10080274
|View full text |Cite
|
Sign up to set email alerts
|

Genetics and Expression Profile of the Tubulin Gene Superfamily in Breast Cancer Subtypes and Its Relation to Taxane Resistance

Abstract: Taxanes are a class of chemotherapeutic agents that inhibit cell division by disrupting the mitotic spindle through the stabilization of microtubules. Most breast cancer (BC) tumors show resistance against taxanes partially due to alterations in tubulin genes. In this project we investigated tubulin isoforms in BC to explore any correlation between tubulin alterations and taxane resistance. Genetic alteration and expression profiling of 28 tubulin isoforms in 6714 BC tumor samples from 4205 BC cases were analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(70 citation statements)
references
References 104 publications
3
67
0
Order By: Relevance
“…We have reported that HuR and TUBB3 are useful predictors of outcome with regard to gemcitabine-and paclitaxel-based regimens in patients with UC (13,17). Similar findings were also reported in other types of cancer (21)(22)(23). However, the present study showed that neither of these markers was individually significantly associated with OS.…”
Section: Relationship Between Overall Survival Periods and Expressisupporting
confidence: 86%
“…We have reported that HuR and TUBB3 are useful predictors of outcome with regard to gemcitabine-and paclitaxel-based regimens in patients with UC (13,17). Similar findings were also reported in other types of cancer (21)(22)(23). However, the present study showed that neither of these markers was individually significantly associated with OS.…”
Section: Relationship Between Overall Survival Periods and Expressisupporting
confidence: 86%
“…Taxenes disrupt microtubule function and genes involved in microtubule setup and assembly, including TUBB1, TUBB4, microtubule‐associated protein 2 (MAP2) and microtubule‐associated protein 4 (MAP4), therefore have a critical role in resistance. TUBB1 was recently described as the gene with the most frequently altered and amplified isoforms in breast cancer . TUBB4 had higher expression in an MCF7 cell line engineered to withstand paclitaxel treatment by administering gradually increasing concentrations of the drug .…”
Section: Discussionmentioning
confidence: 99%
“…Some researches indicated that TUBA1C was implicated in cell proliferation and cell cycle in numerous cancers (26,27). Meanwhile, previous studies demonstrated TUBA1C upregulation could significantly impact tumor growth and progression (28,29). In addition, it was reported that TUBA1C has emerged as a critical intermediary in the cell cycle signaling pathway (21).…”
Section: Discussionmentioning
confidence: 99%